Changes in the utilisation of acute hospital care in Ireland during the first wave of COVID-19. (20th October 2021) - Marron, L; Burke, S; Kavanagh, P
Abstract: Background: Reduced and delayed presentations for non-COVID-19 illness during the COVID-19 pandemic have implications for population health and health systems. The aim of this study was to quantify and characterise changes in acute hospital healthcare utilisation during the first wave of COVID-19 in Ireland to inform healthcare service planning and public health policy. Methods: A retrospective, population-based, interrupted time-trend study was conducted, using two national datasets, from 6th January to 5th July 2020. Results: Comparison between time periods pre- and post-onset of the COVID-19 pandemic within 2020 showed that there were 81, 712 fewer Emergency Department (ED) presentations (-18.8%), 19, 692 fewer admissions from ED (-17.4%) and 210, 357 fewer non-COVID-19 hospital admissions (-35.0%). Reductions were greatest at the peak of population restrictions, at extremes of age and for elective admissions. In the period immediately following the first wave, healthcare utilisation remained below pre-COVID-19 levels however, there were increases in emergency alcohol-related admissions (Rate Ratio 1.22, 95% CI 1.03, 1.43, p-value 0.016), admissions with self-harm (Rate Ratio 1.39, 95% CI 1.01, 1.91, p-value 0.043) and mental health admissions (Rate Ratio 1.28, 95% CI 1.03, 1.60, p-value 0.028). Conclusions: Public health implications of delayed and lost care will become fully apparent over time. In the short-term, backlogs in care need to managed and population health impacts of COVID-19 and associated restrictions, particularly in relation to mental health and alcohol, need to be addressed through strong public health and health system responses, including the adoption of a pandemic recovery plan. In the long-term, COVID-19 has highlighted weaknesses in the health system and is an opportunity to progress reform towards a universal, high-quality, sustainable and resilient health system, capable of meeting population health needs and responding to future pandemics. Key messages: The COVID-19 pandemic impacted non-COVID-19 healthcare utilisation in Ireland with evidence of delayed and lost acute hospital care and increased need for emergency mental health and alcohol services. Population health and health system recovery from COVID-19 is a public health priority.